The Effect of Immunization Programs to Reduce The Number of Cases of Infectious Diseases in The Community - Agus Jalpi; Netty Netty; Achmad Rizal; Hilda Irianty (PT. Anagata Sembagi Education, 2025)
Immunization programs are one of the most effective public health interventions to prevent and reduce the incidence of infectious diseases. This study aims to analyze the effect of immunization programs on the reduction of infectious disease cases in the community. A quantitative method was employed using a descriptive and correlational analysis approach, based on secondary data from health department reports and records of immunization coverage and infectious disease cases over the past five years. The findings indicate a significant correlation between increased immunization coverage and decreased incidence of diseases such as measles, diphtheria, and hepatitis B. The discussion highlights disparities in immunization coverage between regions, the influence of social and educational factors, and implementation challenges in the field. The study concludes that although immunization is proven to be effective, its success relies heavily on supportive policies, community education, and adequate healthcare infrastructure. These findings provide important contributions to strengthening national immunization policies in a more equitable and sustainable manner.